FAKTOR-FAKTOR DETERMINAN PENOLAKAN ORMAS ISLAM TERHADAP UU NO.17 TAHUN 2013 TENTANG ORGANISASI KEMASYARAKATAN (STUDI KASUS MUHAMMADIYAH DAN HIZBUT TAHRIR INDONESIA) - Ramadhanil Haq; Ahmad Taufiq; Puji Astuti (Journal of Politic and Government Studies, 2014)
The presence of community organizations in society is a manifestation of the social movement in Indonesia. In the New Order era, the social organization stipulated in Law No. 8 of 1985. After the reform, the rise of a civil society is the result of restrain freedom by the New Order regime. This led to the coming of organizations each year with a different identity, therefore the government considers this law is considered to be no longer relevant to regulating organizations in Indonesia. So that the Government and the Parliament Act designing new community organizations in lieu of Law No. 8 of 1985, which ultimately resulted in the Law No.17 Year 2013 on Community Organisations. The presence of this new law raises CBOs rejection of the existing organizations in Indonesia, particularly Muhammadiyah and Hizbut Tahrir Indonesia, which is Islamic organizations. The study, entitled " Determinants Factors Against Rejection of Islamic Organizations Act No.17 Year 2013 (Case Study of the Muhammadiyah and Hizbut Tahrir Indonesia) uses a qualitative descriptive study. The purpose of this study was to determine the major factors that led to the Muhammadiyah and HTI reject the existence of Law No.17 Year 2013. This study led to several conclusions that: in general there are the similarities and differences between the two organizations in rejecting the law, ranging from denial of the main reasons to political efforts undertaken. Muhammadiyah reject this law for three reasons: too restrict freedom of association, the setting does not provide legal certainty because many chapters are multiple interpretations and contrary to the law of another product, and excessive government intervention. While Hizb ut-Tahrir Indonesia rejected for two reasons: not impose a single ideological principles, and many chapters are multiple interpretations and overlap. Keywords: islamic organization, social movement, civil society.